Biofuel supply chain design from Coffee Cut Stem under environmental analysis. (1st April 2016) - Duarte, Alexandra; Sarache, William; Costa, Yasel
Abstract: The fossil fuel consumption is still a global concern that has received great deal of attention from Chemical Engineering and Operation Research fields. In this sense, this paper presents a SCND (Supply Chain Network Design) for second-generation biofuel production. For this aim, we proposed a mathematical model that includes, simultaneously, economic and environmental issues. The model feasibility has been tested in Colombia. In this case study, the bioethanol production from Coffee Cut Stem (Coffee-CS) is examined considering the three main echelons of the supply chain. Experimental results showed that Coffee-CS is a profitable and sustainable feedstock for biofuel production. Highlights: An optimization model for supply chain network design is presented. The model analyzes the economic and environmental performance. The optimization process was developed using Coffee Cut Stem as feedstock. A sensitivity analysis is presented in order to evaluate the impact of CO 2 prices variation.